Increasing human papillomavirus vaccination at the recommended age. Issue 5 (29th January 2019) - Lin, Xia; Shrader, Lauren; Rodgers, Loren; Stokley, Shannon; Markowitz, Lauri E.
Abstract: In the United States, human papillomavirus (HPV) vaccine has been recommended for females since 2006 and for males since 2011. However, national HPV vaccination coverage among adolescents is lower than national targets, and many adolescents initiate HPV vaccination later than the recommended age. We analyzed records for >2 million persons born during 1996–2000 who initiated HPV vaccination at age 9 through 16 years from six Immunization Information Systems Sentinel Sites, displayed the distribution of HPV vaccination initiation age, and calculated HPV vaccination coverage. More adolescents in recent cohorts initiated HPV vaccination at the recommended age of 11–12 years, the majority of whom received another recommended vaccine on the same day. However, >40% of all vaccinated adolescents did not initiate the HPV vaccination until age 13 years or later. Continued efforts are needed to increase HPV vaccination initiation at the recommended age.